New Public Management and Human Resource Planning Process In Delta State Hospital Management Board, Asaba, Nigeria - okolie, ugo chuks; EGBON, Thomastina Nkechi; AFONUGHE, Irikefe Omamuyovwi (LPPM Universitas Malikussaleh, 2024)
The new strategy for public management has given rise to a shift in human resource planning. The purpose of the study is to assess how the new public management approach's theoretical modifications have affected its practical applications, particularly in the area of human resource planning. The main goal of this study was to ascertain how the New Public Management approach has affected human resource planning in Delta State Hospital Management Board, Asaba. Convenience sampling and a cross-sectional research design were used. For this study, a questionnaire was used as the research tool for data collection, and 109 respondents were deemed useful. Statistical Package for Social Sciences (SPSS) software version 23.0 was used to perform inferential statistics of correlation and multiple regression analysis on the collected data. The study's findings demonstrated a favorable and significant correlation between new public management and human resource planning and a high-performance culture. The study also showed that the New Public Management approach had a direct impact on the culture of high commitment and performance and human resource planning. The study makes several recommendations, including that the Delta State Hospital Management Board and other related public sector organizations work on clearly outlined HR policies that can form the cornerstone of an institutional framework to ensure the efficient application of HRP policies. Additionally, they should implement New Public Management processes that include human resource planning scope and allocate more funds for the capacity building and professional growth of the resources in order to provide need-based training to their staff. The study is unique in two ways. First, while there are numerous studies that describe the traditional approach to public management in the literature, this study offers a critical viewpoint on it. Second, no other studies in Nigeria have looked into the connection between the new public management approach and human resource planning; the study is a leader in the field in this regard.